Eksplorasi Nilai Filosofis dan Sistem Tukar Koin Kayu sebagai Representasi Etnomatematika di Pasar Sarwono - Hidayah, Yunita Nor; Nisya, Risya Uliatun; Cahayani, Riska Ayuk; Zuliana, Eka (Papanda, 2026)
This study aims to explore the philosophical values and mathematical concepts found in the wooden coin exchange system in buying and selling activities at Sarwono Market, Wonosoco Village, Undaan District, Kudus Regency. The research problem focuses on the relationship between local culture and the application of mathematical concepts in traditional economic practices. The research subjects consisted of one BUMDes manager and five traditional food vendors at Sarwono Market. The method used was qualitative with an ethnographic approach through observation, interviews, and documentation. The data were analyzed using the Miles & Huberman model, which includes data reduction, data presentation, and conclusion drawing, with triangulation of sources and methods to ensure data validity. The results showed that the wooden coin exchange system not only functions as a transaction tool but also represents the values of honesty, accuracy, balance, and responsibility. Mathematically, these buying and selling activities contain the concepts of basic arithmetic operations, comparative values, and the geometric shape of a circle. This study confirms that ethnomathematics plays an important role as a contextual learning approach as well as a means of preserving cultural values and strengthening the local identity of Indonesian communities.